Pasture intensification in beef cattle production can affect methane emission intensity. (15th September 2020) - Sakamoto, Leandro S; Berndt, Alexandre; Pedroso, André de F; Lemes, Amanda P; Azenha, Mariana V; Alves, Teresa C; Rodrigues, Paulo H M; Corte, Rosana R; Leme, Paulo R; Oliveira, Patrícia P A
Abstract: Increasing greenhouse gas (GHG ) emissions from anthropogenic activities have contributed to global warming and consequently to climate change. Among all sources of emissions, the agricultural sector accounts for just under a quarter, mainly because of the intensification of food production systems necessary to supply the growing demand of the population. As ruminal fermentation is the largest source of methane emission in the livestock industry, emission by cattle has become the focus of studies. The aim of this study was to evaluate enteric methane emission and emission intensities of Nellore cattle at different ages submitted to levels of intensification of the grazing system. Twenty-four animals per cycle (age of 21.8 and 13.1 mo in cycles 1 and 2, respectively) were randomly distributed across different grazing systems: irrigated pasture with a high stocking rate (IHS ), dryland pasture with a high stocking rate (DHS ), recovering dryland pasture with a moderate stocking rate (DMS ), and degraded pasture with a low stocking rate (DP ). Methane emission was measured using the sulfur hexafluoride technique in each season of the cycle. Intensive systems provided higher yields of good-quality forage as well as superior animal performance when compared with DP. Methane yields were different between seasons and cycles. Methane emissions per average daily weight gain and dry matter digestible intake were different between treatments. Differences in the results were observed when they were analyzed per hectare, with the highest gain yield ( P = 0.0134), stocking rate, weight gain, carcass production, and total methane emission ( P < 0.0001) being found for the intensive systems. There were no differences in emissions per weight gain or carcass production between production systems, while a difference was observed between cycles ( P = 0.0189 and P = 0.0255, respectively), resulting in lower emission intensities for younger animals. We conclude that more intensive systems resulted in a higher kilograms production of carcass per hectare; however, animals at 19 mo of age raised in the IHS and DMS systems had a lower emission intensity in kilogram of CO2 -eq. per kilogram of carcass. Moderate intensification (DMS) using animals at about 19 mo of age might be an effective strategy to mitigate GHG emissions from Brazilian tropical pastures. Further studies are needed to understand the relationship between increasing productivity and decreasing environmental impacts, especially methane emission from ruminants.